The diakonia of the elder according to 1 Peter - Breed, Gert (AOSIS, 2016)
In this article, the ministry of the elder is investigated according to 1 Peter 5:1-5 from the perspective of the usage of the diakon word group in 1 Peter. Firstly, the place of 1 Peter 5 in the context of the whole letter is examined. Then the connection between 1 Peter 5:1-4 and 1 Peter 4:7-11 is ascertained. That is followed by a detailed exegesis of 1 Peter 5:1-4. It is found that the immediate context (1 Peter 4), indicates that in 5:1-4, Peter describes the diakonia of the elders. Based on the research, guidelines are suggested for the diakonia of the elder according to 1 Peter.
Keywords: Elder; Ministry; Diakon word group; Diakonia; 1 Peter; Leadership; Jesus' teaching